Analisis Pengaruh Earning Per Share, Economic Value Added terhadap Return Saham Selama Pandemik Covid-19 - Dwi Fitrianingsih; Kusmiyatun Kusmiyatun; Tia Kartikasari (Penerbit Goodwood, 2022)
Purpose: This study was to analyze and explain the effects of earnings per share (EPS) and economic value added (EVA), as well as the price-earnings ratio during the Covid-19 pandemic. Method: Descriptive statistical analysis with a quantitative approach. The results of this study show that earnings per share (EPS) and economic value added (EVA) values increased, which were very high during the pandemic but decreased in stock returns. Result: This study also indicate that earnings per share (EPS) and economic value added (EVA), in part or at the same time, have no and no significant effect on stock of food and beverage companies. Limitation: This study is that it covers EPS, EVA, and equity returns for the two years prior to the pandemic and during the Covid-19 pandemic. Contribution: Particularly helpful in providing information on earnings per share (EPS) and economic value added (EVA) which are important parts of a company's analysis that investors should consider when making an investment.